login
a(n) = M(n) - m(n) for n >= 2, where M(n) = max{ a(i) + a(n-i): i = 1..n-1 }, m(n) = min{ a(i) + a(n-i): i = 1..n-1 }.
2

%I #3 Mar 30 2012 18:55:51

%S 1,0,0,1,2,3,3,2,0,3,5,6,6,5,3,4,6,9,7,4,4,6,7,9,8,6,4,7,10,11,10,8,5,

%T 7,10,14,10,7,6,8,10,13,10,8,6,10,13,14,13,11,8,9,12,17,12,8,9,12,13,

%U 15,13,9,8,12,16,17,15,12,9,11,15,20,14,10,10,13,14,18,14,11,9

%N a(n) = M(n) - m(n) for n >= 2, where M(n) = max{ a(i) + a(n-i): i = 1..n-1 }, m(n) = min{ a(i) + a(n-i): i = 1..n-1 }.

%Y Cf. A022909, A022910.

%K nonn

%O 1,5

%A _Clark Kimberling_